Imaging 2004
DOI: 10.1183/1025448x.00030013
|View full text |Cite
|
Sign up to set email alerts
|

The role of positron emission tomography with18F-2-fluoro-2-deoxy-D-glucose in respiratory oncology

Abstract: The role of positron emission tomography with 18 F-¯uoro-2-deoxy-D-glucose in respiratory oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…In order to further assess whether FDG-PET effectively contributes to the high diagnostic yield in the present study, a randomised study comparing TBNA combined with EBUS, with or without prior evaluation with FDG-PET, should be required. One problem with such a study, however, is related to the fact that a PET scan has also been shown to afford significant additional information in the search for metastasis of lung cancer, as well as being cost-effective [4,19].…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further assess whether FDG-PET effectively contributes to the high diagnostic yield in the present study, a randomised study comparing TBNA combined with EBUS, with or without prior evaluation with FDG-PET, should be required. One problem with such a study, however, is related to the fact that a PET scan has also been shown to afford significant additional information in the search for metastasis of lung cancer, as well as being cost-effective [4,19].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…FDG-PET has a sensitivity of 0.85, a specificity of 0.88, a positive predictive value of 0.78, and a negative predictive value of 0.93 [3]. It has then been suggested that a negative mediastinal FDG-PET result may obviate the need for invasive lymph node sampling [4], but a positive one needs to be confirmed [4,5]. In case of positive mediastinal FDG-PET results, further assessment using mediastinoscopy is still considered as the ''gold-standard'' [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of these photons by the PET camera generates the image. The concomitant detection of background gamma photons limits the spatial resolution of small nodules [12,13]. In vitro the minimal detection limit of FDG-PET is about 10 6 cells, which corresponds to a tumor diameter of 1 mm.…”
mentioning
confidence: 99%
“…As a semiquantitive index of FDG uptake, SUV are widely used to differentiate malignant from benign lesions, e.g. in solitary pulmonary lesions, an SUV N2.5 is considered to be evidence of malignancy [8] with a high degrees of accuracy. In the case reported here, while 67 Ga and 99 mTc-scintigram revealed negative findings in the RA, FDG-PET revealed positive findings in the RA accurately, with a SUV 9.89N 2.5.…”
Section: Discussionmentioning
confidence: 99%